AN ANALYSIS OF SOCIO-DEMOGRAPHIC AND CULTURAL FACTORS ON COVID-19 MEASURES IN THE REGION VICTIM OF OUTREACH OF EBOLA DISEASE: EVIDENCE FROM NORTH KIVU PROVINCE OF THE DEMOCRATIC REPUBLIC OF THE CONGO. - bateyi-mustafa, stephane-hans; Onyango.O., Rosebella; Basuayi , Clement Bula (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
Public health measures have been identified as a preventive strategy for influenza pandemics. However, there is no insight related to the role that play socio-demographic, cultural, geographical distance, psychological, behavioural factors towards the low COVID-19 measures. In order to fill this gap in the existing literature review, the present article has used a random sample of 2123 people living in North Kivu, logistic and multiple linear regression to investigate, analyze and assess the effects of socio-demographic, socio-cultural, geographical distance, psychological, behavioural factors that are driving the COVID-19 vaccine in the Province of Nord Kivu, that  was victim of the outreach of  Ebola and pandemic of COVID-19. The results revealed that there was a low adherence of COVID-19 measures, female had 39% (95% CI (0.47;0.79]) decrease to adhere to COVID-19 measures compared to male. Those with age group above 15-24 had higher odds (AOR=3, 95% CI (1.31;5.59]) to adhere to COVID-19 measures than those with age group of 15-24. People with high education had higher odds (AOR=2, 95% CI (0.95;5.53]) to adhere to COVID-19 measures than those with no education. The odds of COVID-19 measures of rural residence occurring decreased by 98% (95% CI (0.06;0.061]) compared to urban residence. Catholic church believers were majority to adhere to COVID-19 measures compared to other churches, geographical distance, psychological, behavioural affect adherence to COVID-19 measures at 30.5%. The results from this study inform policymakers and health system to engage with sensitization, communication and training as strategies for increasing the adherence to COVID-19 measures among females, young and low educated people and both leaders of churches and communities.